Tax and the Electric Car: An Australian case study - Fullarton, Alexander (2018)
This paper considers the impact on tax revenue as a consequence of the changing technology of motor vehicles. As motor vehicles transform their drive trains from internal combustion engines to electric motors their energy source could change from fossil fuel to renewable energy. That may not necessarily be the case. Motor vehicle energy sources may simply move from the on-board, fossil fuelled, internal combustion engines to centralised, fossil fuelled electricity power stations. In that case, fossil fuel consumption, and accompanying greenhouse gas emissions, will continue unabated. Fuel consumption, and its accompanying greenhouse gas emissions, may even increase. Inefficiencies in electricity generation, transmission, storage, as well as losses through storage and use of electricity in the vehicle itself will be added to overall vehicle energy consumption. Regardless of whether the electricity to power the vehicle is sourced from renewable energy, or from fossil fuelled power stations, revenue from motor vehicle fuel excises, currently levied on petroleum products, will fall. In order to continue to build and maintain motor vehicle transport infrastructure governments will be obliged to change their focus pn how road tax revenue is raised. This paper seeks to establish how that energy transition might impact the current tax revenue from motor vehicle fuel taxes. It considers the current number of electric vehicles on Australia roads and predicts what is likely to happen to future motor vehicle fuel excises. It looks at the impact of rising self-generated electricity from renewable energy sources, and how that energy might be used to power electric vehicles in the future. The paper examines data published by the Australian Bureau of Statistics and data provided by the Australian Taxation Office statistics. It also refers to sales data provided by motor vehicle manufacturers. Further, it supports the findings of its analysis of statistical data by a case study of a plug-in hybrid electric vehicle (PHEV) owned by the Solex solar farm project in Carnarvon Western Australia. That data has been collated from fuel and electricity consumptions recorded from delivery of the vehicle in June 2016 to the October 2017. It finds that unless motor vehicles are charged from independent electricity sources, such as dispersed, embedded solar pv installations, little is saved in the way of greenhouse gas emissions. However tax revenues from motor vehicle fuel sales may decline considerably. Although, overall tax revenue may remain consistent, as fuel excises become substituted by goods and services taxes on the sale of electricity. It concludes that as a consequence of the introduction of the electric vehicle, revenue from fuel excise may fall. However, as there has been no official link between road tax revenue and road construction and maintenance expenditure since 1959, the reduction in excise revenue will not necessarily affect funding for the construction and maintenance of roadways by the Australian government.